Motives and self-branding strategies of UPN Veteran Jawa Timur communication science students in building virality on TikTok - Rinda Dwi Pradina; Tazkiyah Azizah (Priviet Social Sciences Journal, 2025)
The phenomenon of self-branding on social media represents a contemporary form of self-representation in which individuals construct and manage their personal identity according to the logic of algorithms and public attention. TikTok, as a participatory and highly visual platform, provides a communicative space for students to practice measurable strategies of digital communication and identity formation. This study aims to explore the motives and analyze the self-branding strategies of Communication Science students at UPN “Veteran” Jawa Timur in constructing viral content on TikTok. This research employed a qualitative descriptive approach within a constructivist paradigm, seeking to understand the subjective meaning of students’ digital communication behavior. Data were collected through in-depth interviews, virtual observations, and content analyses of five TikTok accounts owned by students actively engaged in personal branding. The data were analyzed using Miles and Huberman’s interactive model, which encompasses data reduction, presentation, and conclusion drawing. Theoretically, this research draws on Goffman’s (1959) self-presentation theory and self-branding frameworks (Peters & Khamis) as the primary analytical foundation, supplemented by the uses and gratifications theory to explain the motives behind the use of social media. The findings reveal that students’ motives for performing self-branding include digital self-existence, professional development in creative communication fields, and social validation through audience engagement. The strategies employed involve consistent digital persona creation, algorithmic trend-based content curation, personal storytelling and interactive audience collaboration. Virality is achieved not merely through superficial popularity but through authentic digital identity construction that aligns with the audience’s values and cultural contexts. The study concludes that TikTok serves as a performative arena for communication students to articulate self-competence, test personal narratives and build social capital in the digital sphere. These findings have theoretical implications for the study of digital communication, identity construction, and self-branding strategies in the algorithm-driven era of social media.